Interpersonal Communication: Learning Strategies With Exelearning Still Relevant - Ade Irma Suryani; Jamaris Jamaris; Solfema Solfema (STKIP Taman Siswa Bima, 2023)
Student learning outcomes in geography are generally not maximal and satisfactory, presumably because the learning process does not support students' understanding, that is, too much memorization, and they are not equipped with field practices. This study aims to determine: (1) the learning outcomes of students who are taught inquiry learning strategies using online exe-learning media compared to students who are taught inquiry learning strategies using offline exe-learning media; (2) the learning outcomes of students who have open interpersonal communication compared to students who have closed interpersonal communication; and (3) interaction between learning strategies using exe-learning media and interpersonal communication on student learning outcomes. The research method is quasi-experimental. The results showed: (1) the learning outcomes of students who were taught using inquiry learning strategies using online exe-learning media were higher than the learning outcomes of students taught using inquiry learning strategies using offline exe-learning media with a large influence; (2) the science learning outcomes of students who have open interpersonal communication are higher than the science learning outcomes of students who have closed interpersonal communication with the magnitude of the influence; and (3) there is the interaction between inquiry learning strategies using exe-learning media and interpersonal communication on students' science learning outcomes.